FEATURES OF FORMATION OF THE LOGISTICS MANAGEMENT MECHANISM OF THE ENTERPRISE - ROZOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Logistics, performing various functions, has accompanied mankind at all stages of its development, from military and mathematical activities, and expanding its influence in the economic sphere. In recent decades, domestic and foreign scientists have been studying in particular detail the impact of logistics activities on various spheres of society and in particular the economy. The purpose of the study is to deepen the theoretical foundations, develop guidelines and scientific and practical recommendations for developing a mechanism for managing the quality of logistics activities of the enterprise. The article provides a theoretical generalization and solution of an important scientific problem of the enterprise to develop a mechanism for managing the quality of logistics activities.